2013
DOI: 10.1136/jmedgenet-2012-101415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of the breast cancer genetic risk models BOADICEA, IBIS, BRCAPRO and Claus for predictingBRCA1/2mutation carrier probabilities: a study based on 7352 families from the German Hereditary Breast and Ovarian Cancer Consortium

Abstract: Our results support the use of BRCAPRO and BOADICEA for decision making regarding genetic testing for BRCA1/2 mutations. However, model calibration has to be improved for this population. eCLAUS should not be used for estimating mutation carrier probabilities in clinical settings. Whenever possible, breast tumour molecular marker information should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 36 publications
(36 reference statements)
6
65
2
1
Order By: Relevance
“…Mutation analysis was described by Fischer et al [13] and was performed at a German center for BRCA1 mutation testing (Technical University of Munich, Munich, Germany) according to a standardized protocol. Briefly, high performance liquid chromatography (dHPLC) and sequencing of conspicuous amplicons was employed thus to analyze PCR products comprising all coding exons of BRCA1 .…”
Section: Methodsmentioning
confidence: 99%
“…Mutation analysis was described by Fischer et al [13] and was performed at a German center for BRCA1 mutation testing (Technical University of Munich, Munich, Germany) according to a standardized protocol. Briefly, high performance liquid chromatography (dHPLC) and sequencing of conspicuous amplicons was employed thus to analyze PCR products comprising all coding exons of BRCA1 .…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, for those individuals testing negative for a BRCA1/2 mutation screen who do not have cancer, and are from a family without testing of an affected member, it is not possible to assess the degree of reassurance of a negative test without knowledge of the likelihood that their affected relative was a BRCA1 or BRCA2 mutation carrier. Attempts have been made to incorporate breast pathology into risk algorithms such as the Manchester scoring system [10] and BOADICEA [11, 12] and these improve the accuracy of likelihood estimates and risk thresholds [10, 13]. Periodic revisions of these scoring systems are useful, as most ‘classical’ high penetrance BRCA mutation carrier families will have been identified, leaving less classical phenotypes to be uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from CIMBA and BCAC, we were able to include age-specific distributions of ER and TN status for mutation carriers and the general population. A recent evaluation of BOADICEA for its ability to predict BRCA1 and BRCA2 carrier status showed that the updated BOADICEA model incorporating tumour pathology information, based on the CIMBA/BCAC data distributions, provided a significant improvement in discrimination and re-classification over the previous BOADICEA model without pathology, and that the updated BOADICEA model also performed better than the previous BOADICEA model that incorporated tumour pathology information based primarily on the BCLC data (Fischer et al , 2013). These results suggest that the updated BOADICEA model is a valid tool for use in genetic counselling.…”
Section: Discussionmentioning
confidence: 99%